Solvent extraction of peanut oil: optimization using response surface methodology: article - Abu Samah, Norafikah; Mohd Fuad, Faiznur (2019)
This study focused on seed oil extraction by conventional method and response surface methodology. The study was performed by using different parameters as to find the optimum condition for the extraction process. The parameters that being studied were type of solvent, extraction times, temperature, stirring power intensities and solvent to feed (S/F ml of solvent to gram of feed) ratios. The process parameters were further optimized by statistical approach using historical data design of response surface method (RSM) to find the optimum parameters for the highest oil yield. Results show that maximum oil yield (61%) was obtained by using ethyl acetate as solvent at 18 ml/g of S/F ratio for 25 minutes, 50⁰C and at 700 rotational per minute (rpm). The process was further optimized by surface response method (RSM), the maximum oil yield (72%) occur at 29.07 ml/g of S/F ratio for 29.39 minutes, 45.24⁰C and at 600 rpm.